The Idea of the Middle Class: White Collar Workers and Peruvian Society 1900-1950 - Atack, Peter McKenzie (Labour / Le Travail, 1999)
The article reviews the book, "The Idea of the Middle Class: White Collar Workers and Peruvian Society 1900-1950," by D.S. Parker.